Analisis Behavioral Finance dalam Keputusan Retensi Dana Nasabah Wealth Management pada Bank XYZ - Muhammad Agung Pradana; Joko Ariawan (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Decisions regarding the retention of Wealth management client funds are influenced not only by rational analysis but also by the clients' own behavioral aspects, emotions, and psychological biases. Nevertheless, the role of the Relationship Manager acting as a communication bridge and relationship manager is considered a crucial factor in fostering client loyalty. Research findings indicate that specific aspects of behavioral finance particularly psychological biases such as loss aversion and herd behavior significantly influence clients' psychology when making financial decisions. Field findings suggest that negative biases can be effectively mitigated through high-quality, consistent service and a personalized approach by the Relationship Manager. This study employs a descriptive qualitative method with a case study approach to gain a comprehensive understanding of the phenomenon. Data collection involved in-depth interviews with Wealth management clients at Bank XYZ and the relevant Relationship Managers, supplemented by documentation and a literature review. The study’s implications are intended to serve as a strategic reference for banks managing client funds by incorporating a financial psychology perspective.